An Integrated Air Monitoring Approach for Assessment of Formaldehyde in the Workplace - Stefano Dugheri; Alessandro Bonari; Ilenia Pompilio; Marco Colpo; Nicola Mucci; Giulio Arcangeli (Safety and Health at Work, 2018)
The aim of this study is to validate an integrated air monitoring approach for assessing airborne formaldehyde (FA) in the workplace. An active sampling by silica gel impregnated with 2,4-dinitrophenylhydrazine, a passive solid phase microextraction technique using O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine as on-fiber derivatization reagent, an electrochemical direct-reading monitor, and an enzyme-based badge were evaluated and tested over a range of 0.020–5.12 ppm, using dynamically generated FA air concentrations. Simple linear regression analysis showed the four methods were suitable for evaluating airborne FA. Personal and area samplings in 12 anatomy pathology departments showed that the international occupational exposure limits in the GESTIS database were frequently exceeded. This monitoring approach would allow a fast, easy-to-use, and economical evaluation of both current work practices and eventual changes made to reduce FA vapor concentrations. Keywords: air monitoring, chromatography, electrochemical sensor, enzyme-based badge, formaldehyde